Treatment of vitiligo vulgaris with the combination therapy of topical steroid and vitamin D3 compound - Yoko Konishi; Keiichi Yamanaka; Hitoshi Mizutani (PAGEPress Publications, 2012)
We reported here two cases of vitiligo vulgaris successfully treated with the combination therapy of topical steroid and vitamin D3 compound and currently maintained by vitamin D3 analog without any adverse effects: skin atrophy, striae or telangiectasia on the exposed areas. The best-known mechanism of topical vitamin D3 analog is the enhancement of keratinocytes differentiation and anti-proliferative effects. Vitamin D3 analog is also reported to suppress T-cell mediated immunity, T-cell skin recruitment, and skin infiltration via down-regulating cutaneous lymphocyte antigen expression. Furthermore, vitamin D3 compounds are known to influence melanocyte maturation and differentiation and also to up-regulate melanogenesis. Autoreactive lymphocytes against melanocytes are one of the causes. Topical vitamin D3 analog may control vitiligo itself, however stronger immunosuppressive effects of topical corticosteroid may contribute to rapid re-pigmentation suppressing auto-reactive lymphocytes. The topical combination therapy is a simple, effective and safe option for vitiligo vulgaris in sun-exposed areas.